Microscopic morphology, thermodynamic and mechanical properties of thermoplastic polyurethane fabricated by selective laser sintering - Ruiqi Pan; Lei Yang; Li Zheng; Liang Hao; Yan Li (Materials Research Express, 2020)
Thermoplastic polyurethane (TPU) is one of the elastomeric polymers which has widespread applicability in various fields. Selective laser sintering (SLS) technology is gradually being used to manufacture actual end-use components and enables novel applications (footwear, healthcare mattresses, cable and wire) for TPU. This work aims to explore an optimum protocol (laser power, scanning speed and layer thickness) for SLS fabricated TPU components, and to evaluate the processability of TPU powder through systematically analyzing the morphological properties, structure, melting temperature, crystallization characteristics and tensile properties under different processing parameters. The optimum SLS processing parameters for TPU are laser speed of 3500 mm s ^−1 , laser power of 25 W and layer thickness of 0.1 mm. The tensile strength and superlative toughness of SLS-fabricated TPU samples can reach up to 20.02 MPa and 26 631 J mm ^−3 , respectively. The tensile strength of optimized SLS specimens (parameters: 20 W, 4500 mm s ^−1 , 0.15 mm) has been increased by 87.1% compared to that of reference.